Improving a decree law about coastal zone management in a small island developing state: The case of Cuba (2019)
Cuba is one of the few countries from the Small Island Developing States in the Caribbean region having solid coastal legislation: Decree Law 212 (DL-212) entitled “Coastal Zone Management”. However, that legal framework presents some deficiencies that need to be improved, wherefore an analysis of the major features of DL-212 and the identification of its main issues were conducted in the present study; some ways of implementing the DL-212 in the country were assessed as well. Regarding the Land-Sea Interaction, this work proposes a set of four variables linking geomorphological and human criteria with the aim of improving coastal zone characterization and boundary delimitation. The set of four variables falls into six types of Coastal Geomorphic-typological Units, which are also sub-classified according to the physical aspects and level of territorial urbanization of the Units. Standard nomenclature about boundaries, territorial planning in relation to land-sea interaction is provided in the present research, as well as nine guidelines and eleven recommendations for institutions responsible for physical use planning to implement, in order to obtain a better understanding and implementation of DL-212. The study makes a great contribution to decision-making processes regarding Land-Use Planning, Integrated Coastal Zone Management, and Marine Spatial Planning for future implementation in other Small Island Developing States.